Challenges in the Teaching and Learning of Concord in the Use of English Language - A. Oribabor, O. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
The study analyzed the concord errors in the written composition of J.S.S.III pupils in some selected secondary schools in Abeokuta Central Local Government, Ogun State. It specifically presents the descriptive analysis of socio- demographic characteristics of respondents; investigated the types of concord errors made by J.S.S III pupils in selected secondary schools in Abeokuta Central Local Government, Ogun State; found out the common errors the students make in their essays; and identified the various problems the pupils often encounter in the use of concord. The study utilized both primary and secondary sources of data collection. A simple random sampling technique was used in obtaining information from respondents. The instrument used is questionnaire. A total of seventy two (72) copies of questionnaire were administered on the respondents who were randomly drawn from the population from which sixty two (62) copies were retrieved. A total of sixty (60) scripts were analyzed to identify the problems in writing grammatically correct subject-verb agreement by the students. Secondary data were also sourced from text books, journals, research projects, Newspaper and Magazine and website publications. Data collected were analyzed using descriptive statistical method of analysis such as tabulation and percentages. The study revealed that majority in JSS III Pupils in Abeokuta Central Local Government, Ogun State has problems in applying the rules of concord. Most of the errors committed were under subject verb concord of number and person. The study concluded that teachers should attempt in-service training so that students can write error free essays and students should be given an eloquent and essential English teaching curriculum.